Mendidik Generasi Z: Tantangan dan Strategi di Era Digital - Rizki Heri Prasetyo; Masduki Asbari; Salsabila Amelia Putri (AGUSPATI RESEARCH INSTITUTA, 2024)
This journal aims to explore effective methods in educating children in the current digital era, often referred to as